Professionalism and competing responsibilities: moderating competitive performativity in school autonomy reform - Gobby, Brad; Keddie, A.; Blackmore, J. (2017)
Discourses promoting the benefits of school autonomy have floated freely internationally since moves in the 1980s to greater devolution in the UK, New Zealand, the USA, Australia and Sweden. The most recent Australian version, Independent Public Schools (IPS), grants school leaders more latitude over aspects of their work. But this autonomy is constrained by technologies of competitive performativity, now the norm across Australian and other school systems. Entrepreneurial policies focused on competition, compliance and improved performance make schools, their leaders and teachers, more responsible to external accountabilities. At the same time, autonomy is creatively exercised by leaders due to public service orientations associated with traditional teacher professionalism. This analysis of two Australian case studies of IPS, a secondary school in Queensland and a primary school in Western Australia, illustrates how school leaders navigate conflicting demands of the audit and performance culture by exercising autonomy according to differing notions of professional responsibility, disrupting and moderating the more inequitable priorities and effects prevalent in many performative systems.